Dictators, democrats, and development in Southeast Asia implications for the rest - Rock, Michael T. (Oxford University Press, 2017)
Since 1960 only nine developing countries have succeeded in sustaining high growth. The aim of 'Dictators, Democrats and Development' is to examine how dictators and democrats in three of the nine, Indonesia, Malaysia and Thailand, who share broad similarities with the Rest, built and sustained pro-growth political coalitions.